Metal–organic insertion light initiated radical (MILRad) polymerization: photo-initiated radical polymerization of vinyl polar monomers with various palladium diimine catalysts. Issue 23 (3rd January 2019) - Keyes, Anthony; Dau, Huong; Basbug Alhan, Hatice E.; Ha, Uyen; Ordonez, Estela; Jones, Glen R.; Liu, Yu-Sheng; Tsogtgerel, Enkhjargal; Loftin, Breyinn; Wen, Zhili; Wu, Judy I.; Beezer, Dain B.; et al.
Abstract : The photoinitiated radical polymerization pathway of MILRad polymerization towards its ability to polymerize a variety of vinyl polar functional monomers is investigated. Abstract : Controlled insertion polymerization with organometallic catalysts has served as the foundation for the production of polymers with precise control, and has become ubiquitous in industrial settings. We investigate the photoinitiated radical polymerization pathway of metal–organic insertion light initiated radical (MILRad) polymerization towards its ability to polymerize a variety of vinyl polar functional monomers. A series of Pd-diimine catalysts were synthesized and tested in their ability to produce homopolymers of polar vinyl monomers such as acrylates, methacrylates, acrylamides, styrene, vinyl ethers and vinyl acetate in the dark and under photoinitiation at 460 nm. Acrylates and methacrylates were found to polymerize in the light but not in the dark against all catalysts tested. Acrylamides displayed a stronger dependence on the catalysts structure when polymerized in the light. Other monomer families such as styrene, vinyl ether and vinyl acetate, showed either a limited selectivity and conversions, a prefered cationic polymerization pathway or no reaction. Computational studies were conducted to examine the excited states of the catalysts and the energies associated with those transitions. Results of density functional theory (DFT) and time-dependent DFT (TD-DFT) studies indicate low energy metal-to-ligand charge transfer (MLCT) transitions from Pd–Me σ-bonding into ligand π orbitals leads to reduction of the Pd–Me σ-bond. In this work, we illustrate a dormant radical pathway accessible by all diimine cationic Pd(ii ) catalysts and will expand the scope of MILRad polymerization for the preparation of block copolymers.